2015
DOI: 10.1093/jac/dkv437
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilization of antimicrobial agents on titanium preventsStaphylococcus aureusandCandida albicanscolonization and biofilm formation

Abstract: These data demonstrate the clinical potential of covalently bound VAN and CAS on Ti to reduce microbial biofilm formation without jeopardizing osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 46 publications
1
80
1
2
Order By: Relevance
“…While surfaces to which antibiotics are tethered have demonstrated promise for the potential inhibition of bacterial colonization, it is important to examine if such coated discs affect the growth of hBMSCs, which are an important cell type in bone tissue turnover and regeneration processes (8). One of the disadvantages of antibiotics covalently immobilized on Ti surfaces is that they inhibit hBMSC adhesion and proliferation, and multiple biomolecules must be coimmobilized on the Ti surfaces to achieve multiple biofunctions in order to avoid the disadvantage described above (41).…”
Section: Discussionmentioning
confidence: 99%
“…While surfaces to which antibiotics are tethered have demonstrated promise for the potential inhibition of bacterial colonization, it is important to examine if such coated discs affect the growth of hBMSCs, which are an important cell type in bone tissue turnover and regeneration processes (8). One of the disadvantages of antibiotics covalently immobilized on Ti surfaces is that they inhibit hBMSC adhesion and proliferation, and multiple biomolecules must be coimmobilized on the Ti surfaces to achieve multiple biofunctions in order to avoid the disadvantage described above (41).…”
Section: Discussionmentioning
confidence: 99%
“…Even more, their common use in clinical settings makes them a suitable reservoir for nosocomial infections [35, 36]. Previous studies have demonstrated, to different extents, the efficiency of coating agents, such as chitosan [37], curcumin on dental resins [38], or the covalent immobilization of the antimicrobials vancomycin and caspofungin on titanium [39] preventing C. albicans adhesion and biofilm formation. Thus, we tested various biomaterials under steady-state laboratory conditions as well as physiological flow conditions where the abiotic surfaces were co-incubated or pre-treated with Filastatin.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach consists in immobilizing the drugs on medical surfaces. This has been described for caspofungin on propanal biosurfaces [187] and on titanium substrata which were therefore rendered less susceptible to C. albicans biofilm colonization, at the same time supporting osseointegration (integration of the implant into the bone) [188]. Osteocompatibility is an important trait to be taken into account, the lack of which can limit the clinical use of cytotoxic compounds (e.g., farnesol, [189]).…”
Section: Discussionmentioning
confidence: 99%